Establishment of Rutting Model of Wheel-Tracking Test for Real-Time Prediction of Rut Depth of Asphalt Layers - Yulong Zhao; Ying Gao; Ke Zhang; Yao Zhang; Mingce Yu (Advances in Civil Engineering)
The construction process control of asphalt layers directly affects the road service life and quality. The objective of this study was to establish a rutting model of the wheel-tracking test used for the real-time prediction of the rut depth of asphalt layers in the construction process. The gradation of asphalt mixture, asphalt content, and molding temperature were considered in the development of the new rutting model of the wheel-tracking test. The effects of these three factors on the high-temperature performance of asphalt mixture were analyzed. The order of importance of the factors affecting the high-temperature performance of asphalt mixture is the gradation of asphalt mixture, asphalt-aggregate ratio, and molding temperature. Overall, the predicted values of the rut depth of the wheel-tracking test are very close to the measured values. Furthermore, the difference between the rut depths of asphalt layers of the test group and the control group is small. These comparison results indicate that the new rutting model of the wheel-tracking test has high accuracy and good applicability for the test road.